2020
DOI: 10.3390/ijms21020564
|View full text |Cite
|
Sign up to set email alerts
|

Combined Metabolome and Transcriptome Analyses Reveal the Effects of Mycorrhizal Fungus Ceratobasidium sp. AR2 on the Flavonoid Accumulation in Anoectochilus roxburghii during Different Growth Stages

Abstract: Anoectochilus roxburghii is a traditional Chinese herb with high medicinal value, with main bioactive constituents which are flavonoids. It commonly associates with mycorrhizal fungi for its growth and development. Moreover, mycorrhizal fungi can induce changes in the internal metabolism of host plants. However, its role in the flavonoid accumulation in A. roxburghii at different growth stages is not well studied. In this study, combined metabolome and transcriptome analyses were performed to investigate the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…The experiment is considered to be different when processing ANOVA statistics of 03 replications with p -value < 0.05. Specific primers for analysis were described by Yang et al [ 67 ]; Zhang et al [ 68 ], and Zhang et al [ 69 , 70 ]. The specific gene primers involved in flavonoids biosynthesis-related genes expression are presented in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…The experiment is considered to be different when processing ANOVA statistics of 03 replications with p -value < 0.05. Specific primers for analysis were described by Yang et al [ 67 ]; Zhang et al [ 68 ], and Zhang et al [ 69 , 70 ]. The specific gene primers involved in flavonoids biosynthesis-related genes expression are presented in Supplementary Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Monoterpenoids are present as ubiquitous phytochemicals in the CM extracts, which are characterized by two isoprene units and have the molecular formula C10H16. Among them, morroniside (4), loganin (13), geniposide (14), oxypaeoniflorin (16), paeoniflorin (23) and benzoyl paeoniflorin (47) were precisely identified by comparing with their reference standards, respectively. Moreover, 8-Debenzoylpaeoniflorin (1), mudanoside A (7), debenzoylgalloylpaeoniflorin (12), mudanpioside E (18), paeonolide (22), galloyloxy paeoniflorin (25), galloyl paeoniflorin (31), mudanploside H (37), mudanpioside C (43), benzoyloxypaeoniflorin (44), and mudanpioside J (45) were tentatively identified as monoterpenoids.…”
Section: Chemical Compositions Of CM Extractsmentioning
confidence: 99%
“…As known, the biological efficacy of plant medicine is the result of the overall regulation of a series of phytochemicals. A large number of phytochemicals that are responsible for the bioactivity are affected by the different growth periods [14,15]. It has been found that the optimal time to harvest the P. suffruticosa flower is before the early flowering stage, due to the excellent antioxidant and anti-photoaging activities and the high levels of bioactive phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al profiled metabolome and transcriptome in the symbiosis between a mycorrhizal fungus, Ceratobasidium sp. AR2, and a medicinal orchid, Anoectochilus roxburghii [10]. They concluded that C. sp.…”
Section: Plant-microbial Interactionmentioning
confidence: 99%